Complex presentation of atypical hemolytic uremic syndrome: A case study - Reddy Gangireddy, Venkata; Venkata Varshitha, Bandi; Reddy Annapureddy, Srinivasa; Chadarajupalli, Bhargavi; Reddy Yalamuri, Ravikanth (Indian Journal of Case Reports, 2024)
This case study discusses atypical hemolytic uremic syndrome (aHUS) in a 67-year-old female who presented with hypertension and hyperlipidemia 8 days after a suspected foodborne illness. Her initial presentation included acute respiratory and renal failure in which her condition required extensive re-warming, intubation, pressor or vasopressor therapy, continuous renal replacement therapy or hemodialysis, broad-spectrum antibiotic therapy, and blood and culture workups. Kidney function also showed signs of renal failure, metabolic acidosis, thrombocytopenia, and an elevated level of lactate dehydrogenase in the laboratory results. Radiological investigations demonstrated enteritis, colitis, and an ischemic infarct without hemorrhage. Multidisciplinary consultations achieved the importance and urgency of early diagnosis and treatment of aHUS to prevent irreversible organ damage. This case highlights the role of a timely diagnosis and interprofessional patient care in the treatment of severe aHUS.